Public finance - Seidman, Laurence S. (McGraw-Hill Irwin Boston, 2009)
Public Finance is an approachable text designed with students in mind. The 13 chapters are intentionally written to be taught easily in one semester without skipping material or losing any information. Public Finance contains all the necessary tools and core chapters that are integral to any Public Finance course in a clear and easy-to-read format. The concise sections and lucid examples are engaging for students, without being dense or tedious. This First Edition text incorporates research from across the discipline and provides empirical tie-ins to the real world. The author also covers special topic chapters that define public finance, like education, social security, and healthcare.
Keywords: Finance, Public; Political economy; Income Taxes